Potential and challenges of underground CO2 storage via in-situ mineralization in Switzerland - Adrian Martin; Viola Becattini; Chiara Marieni; Salka Kolbeinsdóttir; Marco Mazzotti; Thanushika Gunatilake (Swiss Journal of Geosciences)
Abstract Carbon Capture and Storage (CCS) technologies play a critical role in achieving global and Swiss climate goals, particularly with Switzerland aiming to domestically store some of its residual CO2 emissions. In situ mineralization presents a promising avenue for stable and permanent CO2 sequestration. This study aims to evaluate the potential of CO2 storage via in situ mineralization in the Swiss underground. A set of technical/geological criteria was defined and used to identify, evaluate, and classify the various geological formations. The selected areas identified and evaluated include alpine tectonic units with large volumes of mafic and ultramafic rocks. Despite the presence of suitable rock types, these units are marked by alpine deformation with highly complex structures, rock mixtures, and complex bedrock hydrogeology. The old, altered, and metamorphic nature of the alpine mafic and ultramafic rock formations results in minimal permeability and porosity, consequently impeding CO2 injectivity and mineralization kinetics, particularly given the low average geothermal gradient. Additionally, challenges related to water resource requirements, storage site location and accessibility, financial costs, regulation, social acceptance, and environmental impacts further impact feasibility negatively. This study concludes that CO2 sequestration via in situ mineralization in the Swiss context is unfeasible in the near term and possibly unsuitable in the long one.